Cooling during exercise enhances performances, but the cooled body areas matter: A systematic review with meta-analyses - Douzi, W.; Dugué, B.; Vinches, L.; Al Sayed, C.; Hallé, S.; Bosquet, L.; Dupuy, O. (Scandinavian Journal of Medicine & Science in Sports, 2019)
Introduction: Hyperthermia during exercise induces central and peripheral fatigue and impairs physical performance. To facilitate heat loss and optimize performance, athletes can hasten body cooling prior (pre-cooling) or during (per-cooling) exercise. However, it is unclear whether per-cooling effect is the same on `aerobic' and `anaerobic' types of exercise (duration < 75s and >76s, respectively according to Gastin (Sports Med 2001;31:725-741) and whether the body area that is cooled makes a difference.